CgMyD88s Serves as an Innate Immune System Plug During Ostreid Herpesvirus 1 Infection in the Pacific Oyster (Crassostrea gigas) - Tang, Xueying; Huang, Baoyu; Lin, Siheng; Wang, Wei; Zhang, Guofan; Li, Li (Frontiers in Immunology, 2020)
Ostreid herpesvirus-1 microvariant (OsHV-1 μVar) is considered a major infectious microbe that can reduce the survival of natural or cultured oysters in summer. Because they lack an adaptive immune system, oysters are dependent on their innate immune systems to fight pathogens. The duplication and functional divergence of innate immune genes in the oyster have been studied, but the contribution of molecular mechanisms underlying innate immunity remains to be defined. Here, we identified the interacting proteins associated with Crassostrea gigas Toll-like receptors (CgTLR) using a yeast two-hybrid screening system. A total of eight proteins were identified that could interact with CgTLR. Three of these appeared at least four times in the screening and were related to MyD88. Two genes encoding these MyD88-like proteins, CgMyD88-1 and CgMyD88-2, possessed typical death and TIR domains. The third gene encoding an MyD88-like protein possessed only a TIR domain, and we named it CgMyD88s. CgMyD88s interacted only with CgTLR but neither CgMyD88-1 nor CgMyD88-2. Both CgMyD88-1 and CgMyD88-2 mRNAs were upregulated after OsHV-1 μVar infection, whereas the expression of CgMyD88s decreased. When overexpressed in HEK293T cells, CgMyD88-1 and CgMyD88-2 activated an NF-κB reporter, whereas CgMyD88s impaired activation induced by CgMyD88-1 or CgMyD88-2. Intriguingly, the silencing of CgMyD88s using double-stranded RNA (dsRNA)-mediated RNA interference increased the expression of CgMyD88-1 and CgMyD88-2. Taken together, our results revealed that CgMyD88-1, CgMyD88-2, and CgMyD88s may all participate in the TLR-mediated innate immune pathway and that CgMyD88s served as a plug to avoid oysters from excessive inflammatory response during OsHV-1 μVar infections.